The Effect Of Quality Of Life And Motivation On Employee Performance With Job Satisfaction As An Intervening Variable At PT Bank Pembangunan Daerah (BPD) Sulawesi Tenggara - Nursahara Juniaeni Khaeruddin; Arif Hartono (International Journal of Economics, Business and Innovation Research, 2024)
This research examines the influence of quality of work life and motivation on employee performance through job satisfaction as an intervening variable at PT Bank Pembangunan Daerah (BPD) Sulawesi Tenggara. This study employed a quantitative methodology, utilizing online questionnaires distributed via Google Forms. The respondents of this study comprised the entire population of 252 respondents. The census technique was used as the sampling methodology to determine the sample. Hypothesis testing in this study was conducted using the SEM-PLS analysis tool through SmartPLS software (v. 4.1.0.6). The results of this study based on data analysis found that 1) the quality of work life has a positive and significant effect on employee performance, 2) motivation has a positive and significant effect on employee performance, 3) the quality of work life has a positive and significant effect on job satisfaction, 4) motivation has a positive and significant effect on job satisfaction, 5) job satisfaction has a positive and significant effect on employee performance, 6) job satisfaction can mediate the relationship between quality of work life and employee performance, and 7) job satisfaction can mediate the relationship between motivation and employee performance.